Jumlah Total Bakteri dan Nutrien Nitrogen Pada Sedimen Mangrove Taman Hutan Raya (TAHURA) Ngurah Rai, Bali - Hanna Santika Tinambunan; Ima Yudha Perwira; Ni Made Ernawati (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
This research aims to find out the total amount of bacteria and nitrogen nutrients found in mangrove sediments in Ngurah Rai Forest Park (TAHURA), Bali. Sampling was conducted in 4 locations, namely from estuary Mertasari, estuary Tukad Mati, estuary Jimbaran, and Nuda Dua, where 1 location consists of 3 sampling points. The research was conducted at the Fisheries Laboratory of the Faculty of Marine and Fisheries of Udayana University in December 2020. The research phase is to prepare research materials, take measurements of ammonia, nitrates, total bacteria, pH, TDS, and electrical conductivity (EC). Measuring pH and TDS/EC using a pH meter and TDS/EC meter. Determining the total number of bacteria using the Total Plate Count. The results showed that the total number of bacteria by 33 × 107 CFU / g and while in nitrogen nutrients obtained from several parameters that have a result in nitrates of 2.8 mg / L, ammonia of 21.5 mg/L, dissolved solids (TDS) of 2100 mg/L,acidity (pH) of 6.6,electrical conductivity (EC) of 4259 ?S/cm. The fertility of mangrove ecosystem in Ngurah Rai Bali Forest Park (TAHURA) can be known from the measurement of physical and chemical parameters in sediment that has been done. Where the content of nitrogen nutrients, such as in the parameters of ammonia and nitrate content contained in mangrove sediment is not classified as polluting the waters because it is still in the category of safe, where the material of organik in sediment can be a source of fertility for mangrove growth.